2000
DOI: 10.1046/j.1365-2141.2000.02183.x
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding symptoms and coagulation abnormalities in 337 patients with AL‐amyloidosis

Abstract: Summary. Haemorrhage is a frequent manifestation of amyloidosis. We performed a retrospective clinical analysis of 337 patients with systemic immunoglobulin light-chain (AL)-amyloidosis, in whom whole-body serum amyloid P component (SAP) scintigraphy and a clotting screen had been performed. Abnormal bleeding was noted in 94 cases (28%), and the coagulation screen was abnormal in 172 cases (51%). The most common abnormalities were prolongation of the thrombin time (TT; 108 cases, 32%) and the prothrombin time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
180
0
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(190 citation statements)
references
References 21 publications
4
180
0
6
Order By: Relevance
“…Six to fourteen percent of AL amyloidosis patients develop an acquired Factor X (FX) deficiency 3, 4, 5. The direct binding/adsorption of FX onto amyloid fibrils has been thought to be a major mechanism for FX deficiency in amyloidosis.…”
mentioning
confidence: 99%
“…Six to fourteen percent of AL amyloidosis patients develop an acquired Factor X (FX) deficiency 3, 4, 5. The direct binding/adsorption of FX onto amyloid fibrils has been thought to be a major mechanism for FX deficiency in amyloidosis.…”
mentioning
confidence: 99%
“…reported series that have indicated Factor X deficiency in 6.3-14% of patients [26,32]. In our experience, 75% of patients with severe Factor X deficiency had hemorrhagic complications, of which 50% were severe and 17% fatal.…”
Section: Discussionmentioning
confidence: 47%
“…In a review of the literature, we have been able to identify 17 cases of splenic rupture associated with amyloidosis reported since 1948 [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Although this number does not define the actual incidence of spontaneous rupture of the spleen in amyloidosis, it suggests the splenic rupture is a rare complication in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported to occur in 6.3-14% of these patients [24,[27][28][29]. Factor X deficiency has long been thought to result from adsorption or the in vivo binding of the factor to the amyloid fibrils [30,31].…”
Section: Primary Amyloidosismentioning
confidence: 99%
“…Recent work by Mumford et al [29] has also shown that the simple adsorptive mechanism for factor X deficiency in amyloidosis may be an oversimplification, and that there may be other mechanisms, including a functional impairment of factor X.…”
Section: Primary Amyloidosismentioning
confidence: 99%